Strengthening of reinforced concrete slabs using carbon fiber reinforced polymers rods and concrete jacket with a mechanical anchorage system - Saeed, Firas Hassan; Hejazi, Farzad; Muhammad Rashid, Raizal Saifulnaz (Elsevier, 2024)
This study presented the development of a new method for strengthening of Reinforced Concrete (RC) slabs using Carbon Fiber Reinforced Polymer rods (CFRP) and an Ultra-High Performance Fiber Reinforcement Concrete (UHPFRC) external jacket with a Mechanical Anchorage System (MAS). The mechanical anchorage system includes two components: high-carbon steel plates and the Mechanical Expansion Anchorage Bolt System (MEABS), and it's employed to prevent any premature de-bonding between the existing concrete surface and the externally strengthening layers (CFRP rods and UHPFRC jacket). The efficiency of the proposed strengthening method was evaluated through conducting an experimental test on a few fortified slabs by applying cyclic loads using a dynamic actuator. For this purpose, three distinct concrete slabs were tested to assess various design parameters, including a control slab, a strengthened slab with the UHPFRC jacket only, and a strengthened slab with CFRP bars at the bottom of the slab with an external UHPFRC jacket. The results of experimental tests reveal that the proposed strengthening system significantly enhanced the load capacity of the slab and prevented premature debonding failures between the old concrete of the slab and the new UHPFRC layer until the stage of slab failure. Accordingly, the new proposed strengthening system played a crucial role in enhancing the tension zone of the slabs and delaying the occurrence of diagonal crack loads. On the other hand, embedding CFRP bars within the UHPFRC jacket in the strengthened slab led to a notable enhancement of 82 % in the ultimate load capacity of the slab. The FE and analytical models were developed to predict the behavior of the specimens. The models' outcomes were in good agreement with the experimental data. Consequently, the new proposed strengthening system emerges as a reliable technique for enhancing the performance of reinforced concrete slabs, eliminating the risk of debonding between old and new parts.